Engineering community college transfer pathways through pre‐transfer programs. Issue 198 (30th March 2022) - Grote, Dustin M.; Richardson, Amy J.; Glisson, Hannah E.; Knight, David B.; Lee, Walter C.; Watford, Bevlee A.
Abstract: Community college scholars and practitioners consistently seek ways to support vertical transfer from community colleges to four‐year institutions. An emerging practice to streamline coursework transfer is the use of tailored, intrusive pre‐transfer advising to increase information access for students still enrolled at the community college. In this article, we explore how one pre‐transfer program—the Virginia Tech Network for Engineering Transfer Students (VT‐NETS)—improved the transfer pathway in engineering through early integration programming and advising structures that help to streamline vertical transfer. Using a quasi‐experimental design, we compare the experience of transfer students who participated in VT‐NETS with transfer students that did not participate in the pre‐transfer program. Based on our findings, we make practical recommendations that may be useful to community colleges and university partners seeking to establish, improve, or scale up early‐integration programs for prospective transfer students.